PREPARATION OF MICROCAPSULE OF CHITOSAN GEL BEADS CROSSLINKED WITH ETHYLENE GLYCOL DIGLYCIDYL ETHER (Psf-Egde-Cts) AS ADSORBENT FOR Procion Red Mx 8b Dye - Kusumaningsih, Triana; Handayani, Desi Suci; Lestari, Yuni (Alchemy Jurnal Penelitian Kimia, 2012)
Microcapsules of chitosan gel beads crosslinked with Ethylene Glycol Diglycidyl Ether (PSF-EGDE-CTS) were prepared to improve adsorption capacity and mechanical stability of chitosan at acidic condition. These microcapsules were prepared through three step i.e. the formation of gel beads (CTS), crosslinked CTS with EGDE (EGDE-CTS) and microencapsulation of EGDE-CTS with Polysulfone (PSF-EGDE-CTS). Product characterizations were carried out using FTIR and SEM. The adsorptions were carried out by variation of pH and contact time in order to determine the optimum condition of adsorption. The yield of Microcapsules PSF-EGDE-CTS was 94,79 wt %. The optimum condition of Procion Red MX 8B dye adsorption by PSF-EGDE-CTS is at pH 5 and 24 hours of contact time. The adsorption capacity of PSF-EGDE-CTS is 40,69 mg/g.